An Analysis Of The Compatibility Of Smart Steps Textbook With The School Level-Based Curriculum - Astuti K B, Esti Puji, Prof. Dr. Endang Fauziati, M.Hum, Aryati Prasetyarini, S.Pd, M.Pd (2013)
This research paper is mainly intended to find out wether the English textbook used for the first grade student of Junior high school "Smart Steps" develops the skills suggested by the School Level-based Curriculum. In line with the objectives of the research, the writer used a descriptive qualitative method. In collecting the data, she used document as the data source. The data sources were analyzed by these steps: (1) finding out the kinds of skill avaliable on the textbook, (2) classifiying them, (3) analyzing them, (4) counting and adding them, (5) giving percentage from the total number, (6) judging whether the data are compatible with the indicators in School Levelbased Curriculum or not, and (7) drawing conclusion and proposing suggestions. The result of the analysis data shows that the percentage of the appropriateness of the skills developed in the textbook is 54,16%. It means that the textbook is compatible with the school level-based curriculum in developing skills.